THE EFFECT OF RADIATION DEFECTS ON THE PHOTOCONDUCTIVITY OF ALLOYED MICRO-NANOCRYSTALLINE SILICON SAMPLES - I.X.Saydoqulov,; J.Z. Mirzarayimov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The creation of thermos and photo sensors that are inexpensive and sensitive to external influences, which form radiation defects in silicon samples, is an urgent task in semiconductor physics and technology. This work employs a radiation irradiation technology to obtain condensed monocrystalline silicon material by irradiating a Janine silicon monocrystal with fast neutrons. This method allows for the targeted modification of the photoelectric parameters of the sample. The use of irradiation methods for technological purposes involves, on one hand, the management of the composition of the resulting defects, and on the other hand, the search for ways to optimize the radiative technological process.